Significant publications in diabetes pharmacotherapy and technology in 2020. Issue 2 (4th March 2023) - Clements, Jennifer N.; Franks, Rachel; Isaacs, Diana; Malloy, Kevin; Meade, Lisa T.; Reece, Sara (Mandy); Reid, Debra J.; Ward, Eileen D.
ABSTRACT: Introduction: The most significant articles on diabetes pharmacotherapy and technology in the peer-reviewed literature from 2020, as determined by a panel of pharmacists with expertise in diabetes care and education, are summarized. Areas covered: Members of the Association of Diabetes Care and Education Specialists Pharmacy Community of Interest were selected to review articles published in prominent peer-reviewed journals in 2020 that most impacted diabetes pharmacotherapy and technology. A list of 37 nominated articles were compiled (22 in diabetes pharmacotherapy and 15 in diabetes technology). Based on discussion among the authors, the articles were ranked based on significant contribution, impact, and diversity to diabetes pharmacotherapy and technology. The top 10 highest ranked publications (n = 6 for diabetes pharmacotherapy and n = 4 in diabetes technology) are summarized in this article. Expert opinion: With the significant number of publications in diabetes care and education, it can be challenging and overwhelming to remain current with published literature. This review article may be helpful in identifying key articles in diabetes pharmacotherapy and technology from the year 2020.